Identification of Dental Problems of Adolf Hitler and Eva Braun - Xavier Riaud (Current Practice in Medical Science Vol. 7, 2022)
Forensic dentistry is a specialist branch of forensic sciences in which dental skills are put at the service of judicial systems mainly for investigative purposes for criminal acts or to identify victims of mass/natural disasters or structurally altered human remains. Its global evolution and modernization requires a comprehensive view of applications and available tools.